Clinical characteristics and outcome of acute appendicitis in children up to five years of age: Acute appendicitis in children up to five years of age - Jonuzi, Asmir; Merdovic, Amir; Ćetković, Asja; Milišić, Emir; Zvizdić, Zlatan (Iranian Journal of Pediatric Surgery, 2025)
Introduction: The diagnosis of acute appendicitis in children up to the age of five is very difficult because the child at this age is not able to adequately express the discomfort and pain they feel and the clinical picture in this period is atypical. The aim of this study is the evaluation of clinical characteristics and outcomes of treatment in children under five years of age who underwent appendectomy because of acute appendicitis. Patients and methods: A retrospective, clinical study was conducted, which included 92 patients under the age of five who underwent appendectomy in the period from 01.01.2010. to 31.12.2021. at the Clinic for Pediatric Surgery of the Clinical Center of the University of Sarajevo. Patients were into two groups depending on the intraoperative finding: uncomplicated and complicated appendicitis group . Comparisons between groups were made based on demographic data, inflammatory and blood picture parameters recorded at admission, clinical history, type of treatment and treatment outcome as well as frequency and type of complications. Results: Of 1428 appendectomies in this period, 92 (6.44%) were performed in children younger than five years. Of these, 71 (77.2%) patients had complicated appendicitis. A statistically significant association was found between increased leukocyte count (p = 0.035) and CRP (p <0.01) in the complicated appendicitis group. Median body temperature (37.5 °C and 38.4 °C; p <0.01), symptom duration (24h and 48h; p < 0.004) and duration of hospitalization (5 days and 8 days; p<0.001) were significantly elevated in complicated compared to uncomplicated appendicitis. The most common symptoms were: pain (96.74%) and vomiting (85.87%). Postoperative complications were reported in 8 (8.70%) cases. There was no mortality. Conclusion: The clinical presentation of acute appendicitis for children aged five years or younger is often unusual, and establishing the proper diagnosis is often delayed. Early diagnosis and prompt surgical intervention can reduce morbidity and mortality rates associated with complicated appendicitis.